Effects of the density, aviary type, breed, and age on the behaviors of laying hens kept in cages - Pereira, Danilo Florentino [UNESP]; Vitorasso, G. [UNESP]; De Magalhaes, M. M. [UNESP]; De Oliveira, S. C. [UNESP]; Miyamoto, B. C B [UNESP] (My University, 2008)
An experiment was carried out in order to investigate the behaviors of laying hens due to the environmental factors of: density inside of the cage, aviary type, breed, and age. The experiment was configured as a factorial 4x2x2x2 study, with treatments being four different ages, two different breeds, two different cage densities, and two different aviaries. The birds' behaviors were recorded using video cameras installed in the cages, using samples of 15 minutes recorded from 12 PM to 4 PM. The observed behaviors, frequency and duration of behaviors (measured in seconds) were identified and noted related to each bird. The study was initiated in March 2007, during four non-consecutive weeks. The observed behaviors were: opening wings, stretching, threatening, ruffling feathers, drinking water, aggressive pecking, eating, running, lying down, stretching head out of the cage, preening, mounting, prostrating, and doing nothing (inactivity). Due to the non-normality of the data recorded, the Kruskal-Wallis statistical test of the MINITAB Statistical Software® was used to compare the medians of the variables. For breed factor, only the durations of the eating presented significant differences (p-value< 0.05). For cage density, there was a significant median difference (p-value< 0.05) for almost all behaviors observed. The average length of time of behaviors was higher for the lowest cage density. However, the frequency of behaviors was lmerfor the lowest cage density. The frequency of the behaviors to preen feathers, to lie down, to drink water and to stretch the head were higher in the aviary, where the groups of birds were smaller. The observed behaviors were particularly affected by experimental factors cage density, and aviary type, which directly affects the available space for each bird.
Keywords: Animal behavior; Animal welfare; Group size; Agriculture; Permanent magnets; Potable water; Statistical tests; Average lengths; Drinking waters; Environmental factors; Experimental factors; Kruskal; MINITAB; Non normalities; P values; Statistical softwares; Birds